2019
DOI: 10.1186/s12957-019-1586-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined hepatocellular-cholangiocarcinoma: a population level analysis of incidence and mortality trends

Abstract: Background The purpose of this study was to explore trends in incidence, incidence-based (IB) mortality, and survival for combined hepatocellular-cholangiocarcinoma (cHCC-CC) utilizing a population-based database to attract people’s attention to this disease. Methods The Surveillance, Epidemiology, and End Results (SEER) database was utilized to investigate the incidence and IB mortality for cHCC-CC from 2000 to 2014. Trends in age-adjusted incidence and IB mortality we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
0
39
2
Order By: Relevance
“…One study reported an increase in the incidence of cHCC-CC among both males and females over recent decades until 2014 in the USA (71).…”
Section: Combined Hepatocellular Cholangiocarcinomamentioning
confidence: 99%
“…One study reported an increase in the incidence of cHCC-CC among both males and females over recent decades until 2014 in the USA (71).…”
Section: Combined Hepatocellular Cholangiocarcinomamentioning
confidence: 99%
“…cHCC-ICC is staged by TNM in a clinical context (as opposed to SEER staging of epidemiological data) using the same staging algorithm as for ICC ( Table 3 ) ( 64 – 66 ). It is difficult to get accurate measures of patient survival without treatment (i.e., the true prognosis) but two large epidemiological datasets from the United States provide some guidance ( 12 , 67 ). Median overall survival (mOS) of patients stratified by the SEER stage for distant, regionalized, and localized cHCC-HCC was 4 months (95% CI, 3–6), 7 months (95% CI, 5–11), and 20 months (95% CI 16–28), respectively ( p < 0.001), with the difference between regionalised and localized explained by suitability for resection ( 12 ).…”
Section: Genetic Characterization and Molecular Biologymentioning
confidence: 99%
“…It is difficult to get accurate measures of patient survival without treatment (i.e., the true prognosis) but two large epidemiological datasets from the United States provide some guidance ( 12 , 67 ). Median overall survival (mOS) of patients stratified by the SEER stage for distant, regionalized, and localized cHCC-HCC was 4 months (95% CI, 3–6), 7 months (95% CI, 5–11), and 20 months (95% CI 16–28), respectively ( p < 0.001), with the difference between regionalised and localized explained by suitability for resection ( 12 ). A similar pattern is seen using TNM staging data from the National Cancer Data Base (NCDB) where mOS was 28.6 m for patients with Stage I disease, 24.2 m for stage II, 7.5 m for stage III and 3.1 m for stage IV ( 67 ).…”
Section: Genetic Characterization and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The classi cation of cHCC-CCA has been modi ed since Allen and Lisa rst described it in 1949, and the World Health Organization (WHO) recently updated its taxonomy [1,3,4]. Because of the rarity of cHCC-CCA, its etiology, clinicopathological features, and prognosis in comparison with other primary liver carcinoma remain unknown [5][6][7][8][9][10][11]. Its recurrence pattern and sites and the optimal treatment for recurrence in particular need to be elucidated [12].…”
Section: Introductionmentioning
confidence: 99%